Cathodic protection of underground steel pipelines by using sacrificial anodes - Mohd Saiful Nizam, Mohamad (2009)
Underground corrosion may cause serious damage to the underground steel pipelines structure. Cathodic protection (CP) method is the most important in order to prevent underground corrosion. In this project, Cathodic Protection by using sacrificial anodes technique will be used to the underground steel pipeline. In this project a study of the performance of magnesium and zinc anodes have been carried out. Besides that, in order to know the effect of coating to the corrosion rate, the specimens of steel pipe have been coats using paint. All of the specimens were buried in the soil with depth 0.2m, pH 5.49. Each sample undergoes underground exposure for 28 days before the surface morphology investigation was conducted using Scanning Electron Microscope (SEM). After the exposure period, cleaning process for all specimens follows prior to the final analysis. Corrosion rates were calculated using weight loss methods for all of the specimens. Magnesium sacrificial anode gives better protection to the steel pipe compare to the zinc anode. The result of the corrosion rate for cathodically protected coated steel pipe by using magnesium anode was lowest which is 0.80 mpy compared to the cathodically protected coated steel pipe with sacrificial zinc anode, the corrosion rate is 2.32 mpy. The result for coated steel pipe without using any anode is 2.71 mpy. The magnesium anode performance yield similar result to the cathodicaly protected for uncoated steel pipe. The corrosion rate for coated steel pipe is around 0.80 mpy to 2.71 mpy which is lowest compare to corrosion rate for uncoated steel pipe is around 9.86 mpy to 15.68 mpy. Surface morphology examinations indicate the type of corrosion occurred on the steel pipe was uniform corrosion and galvanic corrosion. In conclusion, the conjoint use of cathodic protection and coating takes advantage of the most attractive features of each method of corrosion control. Magnesium anodes proves to be more practical anode in applying Cathodic Protection for underground steel pipelines.